Genetic algorithm assisted meta-atom design for high-performance metasurface optics - Yu, Zhenjie; Li, Moxin; Xing, Zhenyu; Gao, Hao; Liu, Zeyang; Pu, Shiliang; Mao, Hui; Cai, Hong; Ma, Qiang; Ren, Wenqi; Zhu, Jiang; Zhang, Cheng (Opto-Electronic Science, 2024)
Metasurfaces,composed of planar arrays of intricately designed meta-atom structures,possess remarkable capabilities in controlling electromagnetic waves in various ways.A critical aspect of metasurface design involves selecting suitable meta-atoms to achieve target functionalities such as phase retardation,amplitude modulation,and polarization conver-sion.Conventional design processes often involve extensive parameter sweeping,a laborious and computationally inten-sive task heavily reliant on designer expertise and judgement.Here,we present an efficient genetic algorithm assisted meta-atom optimization method for high-performance metasurface optics,which is compatible to both single-and multi-objective device design tasks.We first employ the method for a single-objective design task and implement a high-effi-ciency Pancharatnam-Berry phase based metalens with an average focusing efficiency exceeding 80%in the visible spectrum.We then employ the method for a dual-objective metasurface design task and construct an efficient spin-multi-plexed structural beam generator.The device is capable of generating zeroth-order and first-order Bessel beams respec-tively under right-handed and left-handed circular polarized illumination,with associated generation efficiencies surpass-ing 88%.Finally,we implement a wavelength and spin co-multiplexed four-channel metahologram capable of projecting two spin-multiplexed holographic images under each operational wavelength,with efficiencies over 50%.Our work offers a streamlined and easy-to-implement approach to meta-atom design and optimization,empowering designers to create diverse high-performance and multifunctional metasurface optics.